93.8k views
2 votes
Find the derivative of y = 2(x^2) - x + 4 at x = 2​

User Barthy
by
4.8k points

2 Answers

5 votes

Answer:

7

Explanation:

Differentiate using the power rule


(d)/(dx)(a
x^(n)) = na
x^(n-1)

Given

y = 2x² - x + 4, then


(dy)/(dx) = (2 × 2)x - 1 = 4x - 1

At x = 2 ⇒
(dy)/(dx) = (4 × 2) - 1 = 8 - 1 = 7

User Giordani
by
5.0k points
4 votes

Answer:

7.

Explanation:

y = 2x^2 - x + 4

The derivative y' = 2*2x^(2-1) - 1

= 4x - 1

At x = 2 y' = 4(2) - 1 = 7.

User GaryP
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.